KONDISI SOSIAL BUDAYA DALAM PERKEMBANGAN HUKUM ISLAM AL- SHA - Suhaimi Suhaimi (LP2M IAI Miftahul Ulum Pamekasan, 2015)
The discourse of Imam Shafi’is thought becomes a phenomenological discourse toward Moslem thought. He was a clergy developed at the era of Abbasid dynasty, at the era of growth and development of school leader. A thought had ever been developed when he was in Iraq, was named as Qaul Qadim, and a thought when he was in Iraq was named as Qaul Jadid. Al-Shafi’i could sentisize two thoughts of great clergies, Imam Abu Hanifah and Imam Malik. The thought of Abu Hanifah was known that it had a contextual characateristic. Meanwhile, Imam Malik’s thought was mostly known that his ideas were textual